2010
DOI: 10.1097/hjh.0b013e328332b88d
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of multiple renin–angiotensin system genes by Sry

Abstract: We demonstrated that the Sry gene complex on the SHR Y chromosome is a candidate locus for hypertension that accounts for the SHR Y chromosome blood pressure effect. All rat strains examined to date share 6 Sry loci, and a seventh Sry locus (Sry3) appears to be unique to SHR males. Previously, we showed that Sry1 increased activity of the tyrosine hydroxylase promoter in transfected PC12 cells, and Sry1 delivered to adrenal gland of WKY rats increased blood pressure and sympathetic nervous system activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 35 publications
(37 reference statements)
1
61
1
Order By: Relevance
“…The AP-1 transcription factor is not involved in testis determination, but is present and has been shown to be active in the promoters of angiotensinogen (Agt) and other RAS genes [21]. The consensus binding site for SRY co-localizes with OCT4.…”
Section: Potential Novel Sry Functionsmentioning
confidence: 99%
“…The AP-1 transcription factor is not involved in testis determination, but is present and has been shown to be active in the promoters of angiotensinogen (Agt) and other RAS genes [21]. The consensus binding site for SRY co-localizes with OCT4.…”
Section: Potential Novel Sry Functionsmentioning
confidence: 99%
“…In the human and rodent brain, immunohistochemical studies reveal SRY expression in dopamine-abundant regions, such as the SNc, where it localizes within dopamine neurons (7,8). SRY regulates the transcription of genes encoding multiple components of dopamine machinery including tyrosine hydroxylase, aromatic acid dopa decarboxylase, dopamine D2 receptor, and monoamine oxidase A (7,8,25,26). Notably, reducing SRY mRNA levels in the SNc of male rats with antisense oligonucleotides leads to a reversible reduction in the number of dopaminergic cells, associated with motor deficits (8).…”
mentioning
confidence: 99%
“…Harvey reported that oral estradiol intake elevated AngII level in postmenopausal women [37], and Brosnihan found that 17b-estradiol led to downregulation of kidney ACE2 and AGTR1 mRNA in ovariectomized apolipoprotein E-lacking female mice [38]. Additionally, Milsted found that the Sry gene complex on the Y chromosome of a spontaneously hypertensive rat had broad regulating functions to the RAS, including AGT and ACE2 [39]. All these gender-specific factors can have a role in regulation of RAS, and furthermore, the distinct reactions of RAS to ACEIs in different genders.…”
Section: Discussionmentioning
confidence: 99%